Knowledge of Breastfeeding: A descriptive study among mothers in Kirkuk Governorate - Mahmud, nazar (Iraqi National Journal of Nursing Specialties, 2011)
Aims: The present study aims at assessing mothers’ knowledge of breastfeeding in Kirkuk governorate,besides determining the relationship between mothers’ knowledge and some of their demographicattributes.Methodolgy: A descriptive study was used the assessment approach and applied on mothers in Kirkukgovernorate from January 15th 2011 to July 25th, 2011. Non-probability sampling a convenience sample of(72) mothers, attending pediatric general hospital in Kirkuk governorate for following up the health statusof their children, was selected for the purpose of the study. A questionnaire was developed for thepurpose of the study. It was comprised of two parts; the first part includes the mothers' demographicattributes and the second part assessed the knowledge of breastfeeding with (20) True or False questions.A pilot study was carried out for the period of January 15th to 25th, 2011 to determine the questionnairereliability through the use of (Test – Retest). A panel of (8) experts was involved in the determination of thequestionnaire content validity. Data were analyzed through the application of descriptive statistical dataanalysis approach (frequency and percentage), and inferential data analysis approach (chi-square).Results: The study findings revealed that more than half (58.3%) of mothers were young, (45.8%) of themhad completed primary school, more than two-third (84.7%) of them were housewife mothers, (61.1%) ofthem have lived inside Kirkuk city, also (61.1) of mothers have more than one children, (63.9%) of themwere regularly visited primary health care center during antenatal period and only (40.3%) of them havereceived antenatal orientation about breastfeeding. According to the level of knowledge of breastfeeding,(66.7%) of mothers answered correctly all questions about breastfeeding, and there was a highly significantrelationship between health education during antenatal period and mothers’ knowledge of breastfeeding.Recommendations: The study findings highlight the need for excessive health education aboutbreastfeeding during antenatal period and advice the mothers to comply with recommended visits duringpregnancy period.